2010
DOI: 10.3109/01942630903546651
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral States of Children with Severe Disabilities in the Multisensory Environment

Abstract: The purpose of this study was to examine the behavioral states of individual children for evidence of responsiveness within and without a multisensory environment (MSE). Three children in the age range of 3-10 years with severe multiple disabilities participated in the study. A single-system ABAB design was used. Participants' behavioral states, identified by indicators of alertness and responsiveness to context, were observed. Two participants demonstrated no change in their behavioral states with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Two studies used behavioral observations to examine the effect of MSEs on activity and alertness states in people with severe IDD. One study with Level IV evidence took place in a pediatric nursing facility and found no change in behavior state among children in an MSE compared with their regular classroom environment (Tunson & Candler, 2010). The second study had Level III evidence and likewise reported similar levels of activity between living rooms and MSE rooms among adults at residential facilities (Vlaskamp et al, 2003).…”
Section: Activity and Alertness Statesmentioning
confidence: 99%
“…Two studies used behavioral observations to examine the effect of MSEs on activity and alertness states in people with severe IDD. One study with Level IV evidence took place in a pediatric nursing facility and found no change in behavior state among children in an MSE compared with their regular classroom environment (Tunson & Candler, 2010). The second study had Level III evidence and likewise reported similar levels of activity between living rooms and MSE rooms among adults at residential facilities (Vlaskamp et al, 2003).…”
Section: Activity and Alertness Statesmentioning
confidence: 99%
“…; Williams et al . ; Tunson & Candler ), these environments still have the potential to serve as starting points for the process of determining and influencing alertness as described above. In the interactions of individuals with PIMD and their DSPs, different kinds of stimuli (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although other research has focused on the social participation experiences of children and youth with complex communication needs (Batorowicz et al, 2014; Gibson et al, 2014; Teachman & Gibson, 2018), the “recreated experience” method is the first manuscript known to have combined various informants and data collection methods as suggested to focus on the inner worlds of central persons where traditional phenomenological methods to understand lived experience are impossible. Individuals with profound motor, communication, and/or cognitive impairments have primarily been involved in research using positivist orientations (Giacomini, 2012), in the fields of medicine and psychology (Einfeld & Tonge, 1996; Evenhuis, 1997; Murphy et al, 1995; Peavy et al, 1996; Schnakers et al, 2008), where objective cognitive, biological, and behavioral measures are the norm (Braun & Clarke, 2013; Fraser et al, 2011; Schnakers et al, 2008; Tunson & Candler, 2010). For example, researchers have conducted research about the quality of life of individuals with locked-in syndrome which involved the assessment of their experiences through measuring mental and physical health in lieu of whether they were satisfied with their lives (Rousseau et al, 2013).…”
Section: Discussionmentioning
confidence: 99%